2012
DOI: 10.1371/journal.pone.0046872
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Processing of Sounds Explains Behavioral Performance Variations due to Changes in Stimulus Contrast and Selective Attention: An MEG Study

Abstract: Selectively attending to task-relevant sounds whilst ignoring background noise is one of the most amazing feats performed by the human brain. Here, we studied the underlying neural mechanisms by recording magnetoencephalographic (MEG) responses of 14 healthy human subjects while they performed a near-threshold auditory discrimination task vs. a visual control task of similar difficulty. The auditory stimuli consisted of notch-filtered continuous noise masker sounds, and of 1020-Hz target tones occasionally () … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
2
10
0
1
Order By: Relevance
“…For instance, attended sounds embedded in notch-filtered noise elicited a modest increase in the neuromagnetic evoked M1 component, whereas the sustained portion of the response featured a robust increase peaking at 300–400 ms after stimulus onset (Kauramäki et al, 2012). Attentional effects on AEPs and AEFs that were maximal within this time frame have been also demonstrated in a variety of other experimental paradigms (Hari et al, 1989; Arthur et al, 1991; Nahum et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, attended sounds embedded in notch-filtered noise elicited a modest increase in the neuromagnetic evoked M1 component, whereas the sustained portion of the response featured a robust increase peaking at 300–400 ms after stimulus onset (Kauramäki et al, 2012). Attentional effects on AEPs and AEFs that were maximal within this time frame have been also demonstrated in a variety of other experimental paradigms (Hari et al, 1989; Arthur et al, 1991; Nahum et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Attention sets can not only be established for different modalities, input channels or moments in time (for a summary, see Lange, 2013) but for task-relevant sound features as well. Selective N1(m) enhancements have been found for example, when the task required attending a given tone frequency (Kauramäki, Jääskeläinen, & Sams, 2007;Kauramäki, Jääskeläinen, Hänninen, Auranen, Nummenmaa, Lampinen, & Sams, 2012;Okamoto, et al, 2007). It has been also demonstrated that unexpected, taskirrelevant auditory events presented in the same channel as the task-relevant auditory events may disrupt the task-relevant attention set, which leads to the removal of the attentional N1-(and possibly P2) -enhancement for closely following task-relevant events (Horváth & Winkler, 2010;Horváth, 2014aHorváth, , 2014b.…”
Section: Attentionmentioning
confidence: 98%
“…Hillyard, Hink, Schwent, and Picton (1973) found that sounds presented in the attended ear elicited higher amplitude N1 (Näätänen & Picton, 1987) waveforms than those presented in the unattended one. Various studies found similar N1 (and N1m-the magnetic counterpart of N1) enhancements for attention sets induced by various types of task demands (e.g., for attended ears: Rif, Hari, Hämäläinen, & Sams, 1991;Woldorff et al, 1993;Woldorff & Hillyard, 1991; attended frequencies: Kauramäki et al, 2012;Kauramäki, Jääskeläinen, & Sams, 2007;Okamoto, Stracke, Wolters, Schmael, & Pantev, 2007; attended frequency or ear: Ozaki et al, 2004; a given attended moment in time: e.g., Lange, Rösler & Röder, 2003; for a recent summary, see Lange, 2013). A number of studies suggest that the enhancement of the N1 waveform is due to the superposition of different event-related potentials (ERPs) or ERP effects: Besides a "genuine" N1 modulation, an ERP of different origin (Alho, Paavilainen, Reinikainen, Sams, & Näätänen, 1986;Knight, Hillyard, Woods, & Neville, 1981) overlapping the N1-termed processing negativity (PN, Näätänen, Gaillard, & Mäntysalo, 1978), or negative difference (Nd, Hansen & Hillyard, 1980)-also contributes to the amplitude increase.…”
mentioning
confidence: 98%